Preaching in eighteenth-century London - Farooq, Jennifer (Studies in modern British religious history, 2013)
This book looks at the role of preaching culture in eighteenth-century England. Beyond the confines of churches, preaching was heard at political anniversaries and elections, thanksgiving and fast days, and society and charity meetings, all of which were major occasions on the English political and social calendars. Dozens of sermons were published each year, and the popularity of sermons, both from the pulpit and in print, make them crucial for understanding the role of religion in eighteenth-century society. To provide a broad perspective on preaching culture, this book focuses on print and manuscript evidence for preaching in London. The book also explores the impact of sermons on society by looking at contemporary perceptions of preaching, trends in the publication of sermons, the process of the publication and the distribution of sermons, and the reception of sermons